P47 30 day readmission is not an accurate measure of morbidity in cranial meningioma surgery. Issue 3 (14th February 2019) - James, Z; Leach, P; Hayhurst, C
Abstract : Objectives: 30 day readmission rate is a widely adopted marker of quality and performance of acute care, but validity is not well demonstrated. We analysed readmission data following cranial meningioma surgery to assess risk factors for readmission. Design: Retrospective cohort study. Subjects: All adult patients who underwent cranial meningioma resection from January 2015 to December 2017 in a single institution. Methods: Using Welsh Clinical Portal electronic data to identify readmission within and beyond 30 days to both the index hospital and regional hospitals. Causes of readmission were recorded. Results: 160 patients were included (76% female, median age 58). 28 cases were emergency admissions, median length of initial admission 7 days. 26% had seizures at presentation. Total readmission rate was 13.5% (median age 54.5, pre-operative seizure rate 40.1%, median length of readmission 9 days). 13 (59%) patients presented within 30 days and 9 (41%)>30 days. Readmission causes were seizure, neurological deficit, thromboembolic, infection, CSF, bleeding and social. Causes after 30 days were the same except social or neurological deficit. Conclusions: Readmission rates are not associated with age, admission route or initial length of stay. Those who have had seizures are more likely to be readmitted. 41% of readmissions presented outside of the 30 day post-operative time. 30 day readmission rates may not be the most suitable method to demonstrate neurosurgical unit performance in meningioma surgery.